The New Conservatism / Cultural Criticism and the Historian's Debate - Habermas Jurgen; Weber Nicholsen Shierry (The MIT Press, 1989)
Destined to be the most widely discussed intervention into the increasingly heated controversy over the apparent transition from Modernity to Postmodernity. Introduction, Translator's Preface, Neoconservatism, The New Obscurity: The Crisis of the Welfare State and the Exhaustion of Utopian Energies, Heinrich Heine and the Role of the Intellectual in Germany, The Idea of the University: Learning Processes, The Horrors of Autonomy: Carl Schmitt in English, Work and Weltanschauung: The Heidegger Controversy from a German Perspective, Taking Aim at the Heart of the Present: On Foucault's Lecture on Kant's What Is Enlightenment?, Culture of Politics, A Kind of Setting of Damages, Historical Consciousness and Post-Traditional Identity: The Federal Republic's Orientation to the West, Index.